The effect of internal control system’s effectiveness on village government’s performance - Mulyani, Sri, Uskara, A.M, Mulyani, Sri, Akbar, Bahrullah,; Sudraja, . (Opción, 2019)
The present study aims to proof the effect(s) of the internalcontrol system’s effectiveness on village government’s performance,measured through levels of fraudulent activities in village fundmanagement. Data was analyzed using Structural Equation Model(SEM)-LISREL method. The result shows that the lower the internalcontrol effectiveness is, the higher level of fraudulent activities invillage fund management are; which may lead to low performance ofvillage government. In conclusion, an effective internal control systemplays a crucial role in reducing frauds in village fund management.